Association Between Maternal Body Mass and Physical Activity Counseling During Pregnancy - Ruart, Shelly; Sinnapah, Stéphane; Hue, Olivier; Janky, Eustase; Antoine-Jonville, Sophie (Frontiers in Psychology, 2021)
Aims: The antenatal period provides an important opportunity for giving advice on healthy lifestyle choices. However, the prevalence of maternal obesity is increasing, and women report that they do not receive counseling. We investigated the information given to pregnant women on gestational weight gain, physical activity, and nutrition during pregnancy in relation with their initial weight status, current gestational weight gain and diagnoses of either pre-pregnancy overweight/obesity or excessive gestational weight gain. Methods: Cross-sectional survey using a questionnaire. Pregnant participants (n=141) were recruited from a midwife center. They completed a structured questionnaire on the information they received during their pregnancy and we assessed its relationship with their weight. Results: We found that many pregnant women did not receive advice about physical activity, gestational weight gain and nutrition (37.5%, 53.2% and 66.2%, respectively). Women with weight problems (pre-pregnancy overweight/obesity and excessive gestational weight gain) were less targeted for counseling, although more than 80% of the women viewed receiving information on these topics as positive. Also, being informed of a weight problem was associated with a greater chance of receiving information about physical activity, gestational weight gain and nutrition (all p<0.05). However, verbalization of the weight problems was low (14.0% of women with pre-pregnancy overweight were informed of their status). Conclusion: Health professionals should dispense more information, especially on PA and particularly for women with weight problems. Verbalization of the weight problem seems associated with more frequent transmission of information.